1995
DOI: 10.1016/0378-5173(94)00408-w
|View full text |Cite
|
Sign up to set email alerts
|

Improved distribution and reduced toxicity of adriamycin bound to albumin-heparin microspheres

Abstract: Adriamycin (ADR) was formulated in albumin-heparin conjugate microspheres (AHCMS) to improve site-specific delivery and to reduce the toxicity of the drug. The effect of formulating ADR in AHCMS was investigated upon intrahepatic administration to male Wag/Rij rats. After intraveno-portal (i.v.p.) administration of ADR-AHCMS, ADR peak plasma concentrations were reduced 10-fold and ADR tissue levels of non-target tissues were significantly reduced, as compared to i.v.p, administration of the free drug. At an i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…At drug doses that were well tolerated by the rat, single injections with doxorubicin alone (sd-DXR; up to 5 mg/kg) did not lead to a change in cardiac performance whereas multiple injections with low-dose doxorubicin alone (mld-DXR; cumulative dose of 10±20 mg/kg) led to a dose-dependent decrease in cardiac function. Using a similar technique to evaluate ex vivo cardiac function, Cremers et al (1995) could not detect a decrease in the heart function of rats after a single bolus injection (intraveno-portal administration of 7.5 mg/kg DXR) either, in spite of the . 2 Relation between cardiac output (ml kPa min A1 g heart A1 ) and cumulative dose of doxorubicin (mld-DXR; mg/kg).…”
Section: Cardiac Performancementioning
confidence: 99%
See 2 more Smart Citations
“…At drug doses that were well tolerated by the rat, single injections with doxorubicin alone (sd-DXR; up to 5 mg/kg) did not lead to a change in cardiac performance whereas multiple injections with low-dose doxorubicin alone (mld-DXR; cumulative dose of 10±20 mg/kg) led to a dose-dependent decrease in cardiac function. Using a similar technique to evaluate ex vivo cardiac function, Cremers et al (1995) could not detect a decrease in the heart function of rats after a single bolus injection (intraveno-portal administration of 7.5 mg/kg DXR) either, in spite of the . 2 Relation between cardiac output (ml kPa min A1 g heart A1 ) and cumulative dose of doxorubicin (mld-DXR; mg/kg).…”
Section: Cardiac Performancementioning
confidence: 99%
“…Tables 1, 2). Besides dose and the number of injections, factors such as route of administration, rat strain and gender are reported to play a role in the development of extracardiac toxicities (Bertani et al 1982;Cremers et al 1995;van Hoesel et al 1986;Young et al 1989). van Hoesel et al (1986), for example, showed that male rats are more susceptible to DXR-induced kidney damage than female rats; moreover, the rat strain used in their study (LOU/M/Wsl) developed DXR-induced kidney damage in spite of multiple drug injections.…”
Section: Extracardiac Toxicitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…If biodegradable, biocompatible ion-exchange microspheres are used, however, this may not be a problem anymore. Recently ion-exchange albumin-heparin conjugate microspheres (AHCMS) were developed, which were shown to be biodegradable and biocompatible and which could be loaded with ADR up to payloads of 34% [10][11][12][13]. The AHCMS are prepared from a soluble conjugate of albumin and heparin.…”
Section: Introductionmentioning
confidence: 99%